Confidence Forced-Choice and Other Metaperceptual Tasks*. (June 2020) - Mamassian, Pascal
Metaperception is the self-monitoring and self-control of one's own perception. Perceptual confidence is the prototypical example of metaperception. Perceptual confidence refers to the ability to judge whether a perceptual decision is correct. We argue that metaperception is not limited to confidence but includes other judgments such as the estimation of familiarity and the aesthetic experience of sensory events. Perceptual confidence has recently received a surge of interests due in particular to the design of careful psychophysical experiments and powerful computational models. In psychophysics, the use of confidence ratings is the dominant methodology, but other paradigms are available, including the confidence forced choice. In this latter paradigm, participants are presented with two stimuli, make perceptual decisions about these stimuli, and then choose which decision is more likely to be correct. One benefit of confidence forced choice is that it disregards confidence biases to focus on confidence sensitivity. Confidence forced choice might also be a paradigm that will allow us to establish whether confidence is estimated serially or in parallel to the perceptual decision.